2022
DOI: 10.2147/ijgm.s350104
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Disease and Bacterial Metabolic Performance of Gut Microbiota in Middle-Aged and Older Patients

Abstract: Background Gallstone disease (GSD) is more commonly presented in aged people. Purpose The purpose of the study was to explore the insights of metabolic performance of bacterial species from gut microbiota as well as the clinical background in middle-aged and elderly patients with GSD. Patients and Methods This is an observational study concerning 120 research participants. Of those, 90 patients with symptomatic GSD addressed for cholecystecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…are associated with lifestyle and dietary habits, with food high in saturated fat and low in vegetable fiber intake noted. These alterations in the gut microbiota are lately increasingly reported in several hepatobiliary conditions [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 98%
“…are associated with lifestyle and dietary habits, with food high in saturated fat and low in vegetable fiber intake noted. These alterations in the gut microbiota are lately increasingly reported in several hepatobiliary conditions [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 98%
“…Considerable changes in multiple functional bacteria are observed. Bacteria secreting the 7α-dehydroxy enzyme increase, and those lowering cholesterol decrease, leading to increased intestinal absorption of BAs and cholesterol ( 89 ). In middle-aged and elderly patients, decreased number of bacteria producing prebiotics, such as butyrate and acetate/propionate; decreased number of mucin-degrading bacteria; and increased number of bacteria producing endotoxin are observed.…”
Section: Gut Microbiota and Gallbladder Principal Diseasesmentioning
confidence: 99%
“…The interaction between the gut microbiome and bile acids is closely coordinated by the bile acid-gut microbiome axis, suggesting that changes in bile acid composition directly influence the gut microbial environment. Recently, much research has been conducted on the gut microbiome, especially its role as a prognostic/predictive biomarker 16 , 17 . Grigor’eva et al concluded the presence of Helicobacter pylori ( H. pylori ) infection and other gut microbiome components, such as Clostridium , Bifidobacterium , Peptostreptococcus , Bacteroides , Eubacterium , and Escherichia coli , contribute to GB stone formation and affect the development of gallstone disease complications.…”
Section: Introductionmentioning
confidence: 99%
“…Grigor’eva et al concluded the presence of Helicobacter pylori ( H. pylori ) infection and other gut microbiome components, such as Clostridium , Bifidobacterium , Peptostreptococcus , Bacteroides , Eubacterium , and Escherichia coli , contribute to GB stone formation and affect the development of gallstone disease complications. Georgescu et al reported that patients with GB stone disease exhibited alterations in the abundances of several functional bacterial species, that is, reductions in abundances of butyrate, lactate, acetate/propionate, and methane producers, and mucin degrading bacteria, and reductions in microbiome biodiversity indices 17 . Furthermore, studies suggest that UDCA or CDCA treatments may impact gut microbiome composition and diversity.…”
Section: Introductionmentioning
confidence: 99%